Electroacupuncture attenuates surgical pain-induced delirium-like behavior in mice via remodeling gut microbiota and dendritic spine - Yang, Liuyue; Ding, Weihua; Dong, Yuanlin; Chen, Cynthia; Zeng, Yanru; Jiang, Zhangjie; Gan, Shuyuan; You, Zerong; Zhao, Yilin; Zhang, Yiying; Ren, Xinghua; Wang, Shiyu; et al. (Frontiers in Immunology, 2022)
Surgical pain is associated with delirium in patients, and acupuncture can treat pain. However, whether electroacupuncture can attenuate the surgical pain-associated delirium via the gut-brain axis remains unknown. Leveraging a mouse model of foot incision-induced surgical pain and delirium-like behavior, we found that electroacupuncture stimulation at specific acupoints (e.g., DU20+Kl1) attenuated both surgical pain and delirium-like behavior in mice. Mechanistically, mice with incision-induced surgical pain and delirium-like behavior showed gut microbiota imbalance, microglia activation in the spinal cord, somatosensory cortex, and hippocampus, as well as an enhanced dendritic spine elimination in cortex revealed by two-photon imaging. The electroacupuncture regimen that alleviated surgical pain and delirium-like behavior in mice also effectively restored the gut microbiota balance, prevented the microglia activation, and reversed the dendritic spine elimination. These data demonstrated a potentially important gut-brain interactive mechanism underlying the surgical pain-induced delirium in mice. Pending further studies, these findings revealed a possible therapeutic approach in preventing and/or treating postoperative delirium by using perioperative electroacupuncture stimulation in patients.